Unidad agrónoma de gestión y desarrollo Sibaté 2030 (2019)
The following document refers to the study initiated from the capital of Bogotá, to the municipality and foundational square of Sibate, this area has focused on the analysis, especially in the muña reservoir and the skirt of the Sumapaz moor, this sector boxes a much of the inconvenience that has been bothering the population, which are of an environmental nature, the large sections of crops on the slopes of the moor in reserve and protection sectors of the large body of water, the Sumapaz Páramo, and the large volume of black water discharged from the Bogotá river to the muña reservoir, the latter is a factor of great consideration not only for the municipality of Sibate, but for the entire province of Tequendama, since due to its high levels of pollution it has prevented optimal social development , economic and cultural of the region.